Odpowiedź :
Odpowiedź:
[tex]1.\\-3(2-3b)+6b=(b-8)-(4-7b)\\-6+9b+6b=b-8-4+7b\\-6+15b=8b-12\\15b-8b=-12+6\\7b=-6\\\\b=-\frac{6}{7} \\\\\\2.\\4-(1-3e)=-5(e+1)-12\\1-1+3e=-5e-5-12\\\\3e=-5-17\\\\\\3.\\2(2s-8)-(6+4s)+5s-4=3s-3+(7-2s)*2\\4s-16-6-4s+5s-4=3s-3+14-4s\\4s-16-6+5s-4=3s-3+14\\9s-26=3s+11\\9s-3s=11+26\\6s=37\\\\s=\frac{37}{6} \\\\\\4.\\4(a-5)+2[-(a-4)+2(a+3)+a]\\4a-20+2(-a+4+2)(a+3)+a)\\4a-20+2(4+2a+6)\\4a-20+2(10+2a)\\4a-20+20+4a\\\\a=8[/tex]
Odpowiedź:
1.
-3(2-3b)+6b=(b-8)-(4-7b)
- 6 + 9b + 6b = b - 8 - 4 + 7b
7b = - 6
[tex]b = -\frac{6}{7}[/tex]
2.
4-(1-3e)=-5(e+1)-12
4 - 1 + 3e = -5e - 5 - 12
8e = -20
e = - 2,5
3.
2(2s-8)-(6+4s)+5s-4=3s-3+(7-2s)*2
4s - 16 - 6 - 4s + 5s - 4 = 3s - 3 + 14 - 4s
6s = 37
[tex]s = \frac{37}{6}[/tex]
4.
4(a-5)+2[-(a-4)+2(a+3)+a]
To nie jest równanie.